2020
DOI: 10.1038/s41598-019-57098-z
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal and transgenerational effects of dinotefuran on biological parameters and behavioural traits of the mirid bug Apolygus lucorum

Abstract: The mirid bug, Apolygus lucorum, has become a major pest of many crops and fruit trees since the widespread adoption of Bt cotton in northern China. Neonicotinoid insecticides, such as dinotefuran, applied to control this pest may show sublethal effects, but evidence for such effects is lacking. Here, we investigated the sublethal and transgenerational effects of dinotefuran on biological parameters and feeding behavioural traits of A. lucorum using the age-stage, two-sex life table and electrical penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Similarly, EPG studies on mirid bugs do not have a universal naming convention. Earlier A. lucorum studies named waveform families (then termed phases) based on voltage patterns visible to the human eye (e.g., Zhao et al 2011b , Song et al 2017 , Lu et al 2020 ). However, some specific waveforms named therein were not well correlated with specific probing behaviors, so the name and definition of mirid waveforms are still evolving.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EPG studies on mirid bugs do not have a universal naming convention. Earlier A. lucorum studies named waveform families (then termed phases) based on voltage patterns visible to the human eye (e.g., Zhao et al 2011b , Song et al 2017 , Lu et al 2020 ). However, some specific waveforms named therein were not well correlated with specific probing behaviors, so the name and definition of mirid waveforms are still evolving.…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal concentrations of insecticides can affect many physiological parameters such as development, longevity, and fecundity (Zhou et al 2017;Lu et al 2020;Wu et al 2022), as well as mobility (da Silva et al 2022), and feeding behaviour (Koo et al 2015;Zeng et al 2016). These effects can vary according to the species and the insecticides used.…”
Section: Introductionmentioning
confidence: 99%
“…These effects can vary according to the species and the insecticides used. For example, sublethal concentrations of dinotefuran can reduce the fecundity of the planthopper Nilaparvata lugens (Stal) (Bao et al 2009) whereas no effect was observed on the mirid bug Apolygus lucorum (Meyer-Dur) (Lu et al 2020). In contrast, other studies have shown that sublethal concentrations of insecticides can stimulate pest population dynamics (e.g., insecticide-induced hormetic responses) by influencing their reproductive output.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the transgenerational population growth of Rhopalosiphum padi L. was observed when these insects were sub-lethally exposed to LD 10 and LD 20 doses of dinotefuran (Deng et al, 2019). Exposure to the LC 30 of dinotefuran significantly extended the developmental duration from the third instar to adult Apolygus lucorum Meyer-Dür in the parental generation (F 0 ), but prolonged the oviposition period and male adult longevity as well as reduced the nymphal survival rate (Lu et al, 2020). Sublethal concentrations (LC 25 ) of sulfoxaflor can significantly increase the developmental duration in the first-generation progeny of Myzus persicae Sulzer and improve the reproductive capacity of adults (Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%